ATP-sensitive potassium channels mediate the thermosensory response of orexin neurons - Parsons, Matthew P (Blackwell Science Inc, 2012)
High body temperatures are generally associated with somnolence, lethargy, hypophagia and anhedonia. Orexin neurons have been suggested to play a role in such sickness behaviours due to their known functions in appetite, behavioural and autonomic activation. Furthermore, the activity of orexin neurons is inhibited by lipopolysaccharide that induces fever. However, the cellular mechanism(s) underlying this suppression of orexin neurons was unknown. We used patch-clamp recordings in acute rat brain slices to demonstrate that orexin neurons, including those projecting to the wake-promoting locus coeruleus, are inhibited by increasing the ambient temperature by a 2–4°C increment between 26 and 40°C. This effect was not mediated by conventional thermosensing mechanisms but instead involved the activation of ATP-sensitive potassium (KATP) channels. Since KATP channels can also sense energy substrate levels and cellular metabolism, our results suggest that orexin neurons can integrate the state of energy balance and body temperature, and adjust their output accordingly. Thus, the thermosensitivity of orexin neurons may be an important part of maintaining energy homeostasis during hyperthermia and fever.